An application of discrete wavelet transform and support vector machines algorithm for fault locations in underground cable - Apisit, C.; Pothisarn, C.; Ngaopitakkul, A. (My University, 2012)
This paper proposes a technique using discrete wavelet transform (DWT) and support vector machines (SVM) for fault location in underground distribution cable. The ATP/EMTP is used to simulate fault signals. The mother wavelet daubechies4 (db4) is employed to decompose high frequency component from these signals. The maximum coefficient obtained from positive sequence current in first scale capable of detecting fault of each bus is used as input pattern for the training pattern. It is shown that the proposed technique gives satisfactory results, and will be very useful in the development of a power system protection scheme. © 2012 IEEE.
Keywords: Fault Location; Support Vector Machines; Underground Distribution Cable; Wavelet Transform